The Relationship Between Social Support from Peers and Learning Outcomes of Trainees at LPK Smart College Padang - Aulia Putri, Rara; Setiawati, Setiawati (Universitas Negeri Padang, 2024)
This research was motivated by the low learning outcomes of training participants at LPK Smart College Padang, this was caused by a lack of communication between training participants. This research aims to: 1) determine the description of the social support of trainee participants at LPK Smart College, 2) determine the description of the learning outcomes of trainees at LPK Smart College, 3) see the relationship between peer social support and the learning outcomes of trainees at LPK Smart College. This research uses a quantitative approach with a correlational type. The population of this research is all 20 registered and active training participants in training in 2023 at LPK Smart College. The sampling technique uses saturated sampling, namely the entire population is taken as a sample. The data collection technique uses a questionnaire and the data collection tool uses a questionnaire which contains a list of statements. The data analysis technique in this research uses percentage and rank order formulas. The results of this research show that: 1) the peer social support received by trainees at LPK Smart College is categorized as quite low, 2) the learning outcomes of trainees at LPK Smart College Padang are categorized as low, 3) there is a significant relationship between peer social support with the learning outcomes of training participants at LPK Smart College.